Islamic Values, Social Influence, and Self-Regulation as Determinants of Online Shopping Addiction among Indonesian University Students - Hasyim, Baso; Assaad, Andi Sukmawati; Hardivizon, Hardivizon; Mustaming, Mustaming (Jurnal Ilmiah Peuradeun, 2025)
Online shopping addiction has become a significant behavioral issue among university students, driven by the rapid growth of digital marketplaces and the pervasive influence of social media. This study examines the role of Islamic values, social influence, and self-regulation in predicting online shopping addiction, with consumptive behavior as a mediating factor. Employing a quantitative correlational design, data were collected from 160 university students in Palopo City, Indonesia, and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that stronger self-regulation and higher adherence to Islamic ethical principles significantly reduce both consumptive behavior and online shopping addiction, while greater social influence increases susceptibility to compulsive purchasing. The study highlights that moral-ethical frameworks, particularly Islamic values, combined with psychological resilience and social awareness, are essential in mitigating excessive digital consumption. By integrating perspectives from behavioral science, social theory, and Islamic ethics, this study offers theoretical and practical contributions for higher education institutions, policymakers, and digital platform designers to promote responsible online shopping practices among youth in religiously rooted societies.